2004
DOI: 10.1039/b403237c
|View full text |Cite
|
Sign up to set email alerts
|

The Kemp elimination in membrane mimetic reaction media. Probing catalytic properties of cationic vesicles formed from a double-tailed amphiphile and linear long-tailed alcohols or alkyl pyranosidesElectronic supplementary information (ESI) available: Further experimental details and figures. See http://www.rsc.org/suppdata/ob/b4/b403237c/

Abstract: The Kemp elimination in membrane mimetic reaction media. Probing catalytic properties of cationic vesicles formed from a double-tailed amphiphile and linear long-tailed alcohols or alkyl pyranosides Klijn, JE; Engberts, Jan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 72 publications
(76 reference statements)
0
8
2
Order By: Relevance
“…This hypothesis was further confirmed by detailed kinetic studies on the same elimination reaction performed in the presence of positively charged DODAC vesicles in which different amounts of negatively charged DDP (Table ) were mixed . The introduction of various other additives, such as linear alcohols and alkyl pyroanosides, led to changes in the vesicular catalysis reflecting its dependence on the molecular properties of the interface between the vesicle and bulk water 7 …”
Section: 31 Reactions In or At The Vesicle Membranementioning
confidence: 72%
See 1 more Smart Citation
“…This hypothesis was further confirmed by detailed kinetic studies on the same elimination reaction performed in the presence of positively charged DODAC vesicles in which different amounts of negatively charged DDP (Table ) were mixed . The introduction of various other additives, such as linear alcohols and alkyl pyroanosides, led to changes in the vesicular catalysis reflecting its dependence on the molecular properties of the interface between the vesicle and bulk water 7 …”
Section: 31 Reactions In or At The Vesicle Membranementioning
confidence: 72%
“…The group of Engberts has employed surfactant aggregates as simple enzyme mimics, with the aim of understanding the efficiency of (artificial) enzymes in terms of desolvation effects, entropy factors, etc. For that reason, the Kemp elimination (Scheme ) was studied in the presence of aggregates formed by a series of surfactants. With respect to the reaction in pure water at the same pH, the elimination rate was increased up to 850 times. It turned out that vesicles were more effective catalysts than micelles, likely providing a more apolar microenvironment at the substrate binding sites for the deprotonation of the substrate.…”
Section: 31 Reactions In or At The Vesicle Membranementioning
confidence: 99%
“…An additional benefit of using long-chain alcohols rather than short-chain alcohols is that there would be little or no chain disordering, a common phenomenon caused by short to medium chain length alcohols . Previous studies on the influence of long-chain alcohols on the gel-to-fluid phase-transition temperature and on the enthalpy change of single- and double-tailed ionic surfactants have also shown that at low n -alcohol concentrations, the transition temperature and Δ H values are reduced, but at high concentrations, the trend displayed by the T m values is reversed. Therefore, n -alcohol appears to have disrupted the local packing and average distance between the surfactant molecules, as will be discussed below based on the analyses of SAXS data.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The decision to prepare vesicles containing 50 mol % of C 12 Glu is rather arbitrary, but at this mole fraction, the concentration of glucoside in the Stern region is high, without preventing the formation of micelles. In addition, it allows comparison with previous work . Experiments were performed at 35 °C, since this is above the main phase transition temperature of all amphiphilic components.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, fewer details of vesicular catalysis are known. In previous studies, we examined the reaction of 5-nitrobenzisoxazole with hydroxide ions in (synthetic) cationic vesicles in the presence of anionic amphiphiles, and the biologically relevant additives cholesterol, long linear alcohols, and sugar-based surfactants. In general, large rate accelerations (about 10 3 ) are observed when the maximum observed rate constant is compared to the observed aqueous rate constant.…”
Section: Introductionmentioning
confidence: 99%